An epistemology of patient safety research: a framework for study design and interpretation. Part 2. Study design. Issue 3 (2nd June 2008) - Brown, C; Hofer, T; Johal, A; Thomson, R; Nicholl, J; Franklin, B D; Lilford, R J
Abstract : This is the second in a four-part series of articles detailing the epistemology of patient safety research. This article concentrates on issues of study design. It first considers the range of designs that may be used in the evaluation of patient safety interventions, highlighting the circumstances in which each is appropriate. The paper then provides details about an innovative study design, the stepped wedge, which may be particularly appropriate in the context of patient safety interventions, since these are expected to do more good than harm. The unit of allocation in patient safety research is also considered, since many interventions need to be delivered at cluster or service level. The paper also discusses the need to ensure the masking of patients, caregivers, observers and analysts wherever possible to minimise information biases and the Hawthorne effect. The difficulties associated with masking in patient safety research are described and suggestions given on how these can be ameliorated. The paper finally considers the role of study design in increasing confidence in the generalisability of study results over time and place. The extent to which findings can be generalised over time and place should be considered as part of an evaluation, for example by undertaking qualitative or quantitative measures of fidelity, attitudes or subgroup effects.